Applications of 3D printing on craniofacial bone repair: A systematic review. (January 2019) - Maroulakos, Michael; Kamperos, George; Tayebi, Lobat; Halazonetis, Demetrios; Ren, Yijin
Abstract: Objectives: Three-dimensional (3D) bioprinting, a method derived from additive manufacturing technology, is a recent and ongoing trend for the construction of 3D volumetric structures. The purpose of this systematic review is to summarize evidence from existing human and animal studies assessing the application of 3D printing on bone repair and regeneration in the craniofacial region. Data & sources: A rigorous search of all relevant clinical trials and case series was performed, based on specific inclusion and exclusion criteria. The search was conducted in all available electronic databases and sources, supplemented by a manual search, in December 2017. Study selection: 43 articles (6 human and 37 animal studies) fulfilled the criteria. The human studies included totally 81 patients with craniofacial bone defects. Titanium or hydroxylapatite scaffolds were most commonly implanted. The follow-up period ranged between 6 and 24 months. Bone repair was reported successful in nearly every case, with minimal complications. Also, animal intervention studies used biomaterials and cells in various combination, offering insights into the techniques, through histological, biochemical, histomorphometric and microcomputed tomographic findings. The results in both humans and animals, though promising, are yet to be verified for clinical impact. Conclusions: Future research should be focused on well-designed clinical trials to confirm the short- and long- term efficacy of 3D printing strategies for craniofacial bone repair. Clinical significance: Emerging 3D printing technology opens a new era for tissue engineering. Humans and animals on application of 3D printing for craniofacial bone repair showed promising results which will lead clinicians to investigate more thoroughly alternative therapeutic methods for craniofacial bone defects.